Avian diversity at highland conservation area of Payeh Maga, Lawas, Sarawak, Malaysia - Rosli, Zamri; Waseem Razzaq Khan, .; Ishfaq Ahmad Khan, .; Rajpar, Muhammad Nawaz; Gerusu, Geoffry James; Alhassan, Abdullahi Bala (Forestry Department Peninsular Malaysia, 2023)
Most tropical montane forests are ideal habitats for a diversity of native bird species. Some of them have been threatened or endangered with extinction by habitat loss and the impact of climate change. The endemic and native bird species are bioindicators, i.e., their occurrence may indicate the current status of the forest ecosystem's health. The current study was carried out in the Lower Montane Forest in Payeh Maga Highland Lawas, Sarawak, to ascertain the bird species composition and diversity using the mist-netting method, to comprehend the ecological significance of the tropical montane forests. In total, 465 individuals from 61 species and 25 families were caught through the mist nets. Out of the total, 237 individuals from 20 species were classified as endemic to Borneo. Five species were identified as "Near Threatened" based on IUCN conservation status. The two families Sylviidae (six species) and Dicaeidae (five species), were the most diverse families in the study area. The Chesnut-crested Yuhina (Staphidae everetti), Chestnut-hooded Lauhingthrush (Pterorhinus treacheri), and Pale Faced Bulbul (Pycnonotus leucops) were three foremost abundant species, i.e., each accounted 56 individuals (12.04), 42 individuals (9.03), and 38 individuals (8.17) of the total population. The finding revealed that the Lower Montane Forest has H' = 3.4 species diversity. This indicated that the Lower Montane Forest, Payeh Maga is a significant habitat for avian species from a conservation perspective. To preserve this prestigious highland, it must be considered to be designated as a National Park or High Conservation Value Forest (HCVF).